Assessment of gastric-acid suppressants prescribing at an internal medicine service of a tertiary hospital in Latin America: A retrospective record review study - Piñerúa-Gonsálvez, Jean Félix (2023)
Gastric-acid suppressants are one of the most frequently used classes of drugs worldwide. Several studies about their overprescribing have been carried out in recent years. The aim of the study was to assess the appropriateness of these drugs at an internal medicine service of a tertiary hospital in Venezuela. A retrospective record review of patients admitted to the internal medicine service from January 2020 to February 2021 was performed. Data about indications for gastric-acid suppressants, the type used, and their continuation at discharge were collected. The prescribing was grouped into two categories, appropriate or inappropriate, according to current clinical guidelines. Of the 1203 patients who were newly prescribed gastric-acid suppressants in hospital during the study period, 993 (82.5%) had an inappropriate prescription. Prophylaxis of peptic ulcers in low-risk patients was the most frequent no evidence-based indication (20.24%). Seven hundred sixty-two patients were discharged on gastric-acid suppressants. Of these, 74.7% did not have an acceptable indication to continue this treatment on an outpatient basis. Many hospitalized patients in a Venezuelan academi re given gastric acid suppressants not in accordance with the current clinical practice guidelines.